Evaluation of early maturing soybean (Glycine max) germplasm accessions for fatty acid composition - KUMAR, VINEET; RANI, ANITA; PANDEY, VIMAL; SINGH, ASHUTOSH; HUSSAIN, S M; CHAUHAN, G S (The Indian Journal of Agricultural Sciences, 2011)
Among unsaturated fatty acids present in soybean oil, linolenic acid is the most Vulnerable while oleic acid is the least susceptible to oxidation. Hence, globally, soybeans with low linolenic acid and high oleic acid are being searched. Fifty nine early maturing soybean germplasnllines were selected from germplasm field of National Research Centre for Soybean and the seeds harvested on their respective maturity were analysed for fatty acid composition and the oil quality parameters, viz monounsaturated (M) :polyunsaturated fatty acids (P), a ratio indicating the oxidative stability of vegetable oils, and linoleic acid (n-6 orw6) : linolenic acid (n-3 orw3), a ·ratio important from health point of view, were computed. Genotypic variation was observed for all the five major fatty acids ofsoybean, namely palmitic, stearic, oleic, linoleic and linolenic acid content. Six germplasm lines, viz EC175330, EC39490, AGS2, IC222, P955and WT142 exhibited oleic acid more than 35%. M/P ratio ranged from 0.21 for EC481306 to 1.33 for EC39490 while linoleic acid (n-6 orw6) / linolenic acid (ri-3 or w6) ratio ranged from 5.45 for EC313976 to 10.10 for EC3339 I9. One-year data indicates that soybean germplasm lines EC39490 and AGS2 that exhibited oleic acid more than 45% may be employed for developing varieties with improved oxidative stability.